Srategi Pembelajaran Berbasis AI dalam Pendidikan Islam - Darayani Afifah Dongoran; Kartika Syafitri; Gusmaneli Gusmaneli (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
The advancement of Artificial Intelligence (AI) has brought significant changes to various aspects of life, including the field of education, particularly Islamic Education. This study aims to explore various AI-based learning strategies that can be implemented to create a more effective, interactive, and contemporary learning process. The method employed in this study is a literature review by examining various scholarly sources, such as journals, books, and academic articles discussing the implementation of AI in education. The findings indicate that the integration of AI can be realized through personalized learning tailored to students’ needs, the use of chatbots as learning assistants, the analysis of students’ progress and learning outcomes, as well as the utilization of technology-based learning media. These strategies are not only capable of improving students’ cognitive aspects but can also strengthen the internalization of Islamic values when applied appropriately and systematically. Furthermore, this study emphasizes that teachers’ technological competence, infrastructure readiness, and the development of an adaptive curriculum are crucial factors in the successful implementation of AI-based learning within the context of Islamic Education.